Leonora Carrington and Goliarda Sapienza: anarchic bodies - McIntyre, H (2022)
This thesis brings together two little-know figures in the history of 20th-century literature: Leonora Carrington (1917-2011) and Goliarda Sapienza (1924-1996). Building on recent academic and public interest in both women, this research offers a new perspective by reading their literary work outside of its immediate cultural context.